2001
DOI: 10.1007/bf02375484
|View full text |Cite
|
Sign up to set email alerts
|

Phase relations, ionic transport and diffusion in the alloys of Cu2S-Ag2S mixed conductors

Abstract: Abstract.Results are reported of the phase relations in the (Agx.~2Cu~.x)2 S system, ionic conductivity, self-diffusion and chemical diffusion coefficients for the solid solutions as a function of the composition x, degree of non-stoichiometry 8, and temperature in the range 473 -673 K. The extensions of the homogeneity regions for single-phases are determined. Total and partial ionic conductivity values are given for copper and silver ions for the solid solutions. Measurements ot" the self-diffusion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Note that diffraction results on a number of copper and silver based chalcogenides and halides (for instance, results of [17][18][19][20][21]) imply that the ionic conductivity can be sensitive to details of the cation redistribution between available interstitial sites versus temperature as well as to the stoichiometry of the material. Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17].…”
Section: Bcc-ag 3 Cussupporting
confidence: 81%
See 3 more Smart Citations
“…Note that diffraction results on a number of copper and silver based chalcogenides and halides (for instance, results of [17][18][19][20][21]) imply that the ionic conductivity can be sensitive to details of the cation redistribution between available interstitial sites versus temperature as well as to the stoichiometry of the material. Taking this into account, we suggest a correlation between the results of the electrochemical measurements from Kadrgulov et al [3], which revealed only a relatively modest increase in the ionic conductivity with temperature within fcc-(Ag x Cu 1-x ) 2 S, and our diffraction results, which show no pronounced cation redistribution. The same correlation was supposed for related superionic fcc-AgCuSe [19], fcc-AgCuS [21] and fcc-(AgI) x -(PbI 2 ) 1-x with x= 5 4 and 3 2 [17].…”
Section: Bcc-ag 3 Cussupporting
confidence: 81%
“…Neutron and synchrotron diffraction data collected at 473 K were used. The refinements were based on Im 3 m symmetry with the S 2− located in the 2(a) sites at (0, 0, 0 3 . All these models were unstable in the refinement due to high correlations between the fitted parameters and produced very poor fits to the experimental data.…”
Section: Bcc-ag 3 Cusmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, ionic conductivities of (Ag x Cu 1Àx ) 2 S compounds, with x=0; 0.2; 0.4; 0.6 and 1, had been studied by Kadrgulov et al. The superionic face-centered cubic phases of these compounds showed negligible dependence on temperature [9]. Recently, Trots et al investigated the phase transition behaviors of silver copper sulfide in a wide range of temperature [10][11][12].…”
Section: Introductionmentioning
confidence: 97%